Observation of convection phenomenon by high-performance transparent heater based on Pt-decorated Ni micromesh - Han-Jung Kim; Dong-Ik Kim; Sam-Soo Kim; Young-You Kim; Sung-Eun Park; Gyuseok Choi; Dong Wook Lee; Yoonkap Kim (AIP Advances, 2017)
In this study, we report for the first time on the convection phenomenon for the consistent and sensitive detection of target materials (particulate matter (PM) or gases) with a high-performance transparent heater. The high-performance transparent heater, based on Pt-decorated Ni micromesh, was fabricated by a combination of transfer printing process and Pt sputtering. The resulting transparent heater exhibited excellent mechanical durability, adhesion with substrates, flexibility, and heat-generating performance. We monitored the changes in the PM concentration and temperature in an airtight chamber while operating the heater. The temperature in the chamber was increased slightly, and the PM2.5 concentration was increased by approximately 50 times relative to the initial state which PM is deposed in the chamber. We anticipate that our experimental findings will aid in the development and application of heaters for sensors and actuators as well as transparent electrodes and heating devices.